Rediscovery of Hieracium scorzonerifolium subsp. divaricatum (Asteraceae), a neglected hawkweed endemic to the Pollino National Park (Southern Italy) - Gristina, Emilio Di; Barone, Giulio; Bajona, Enrico; Gottschlich, Günter (Phytotaxa, 2025)
The occurrence of Hieracium scorzonerifolium subsp. divaricatum, an endemic taxon of the Pollino National Park (Southern Italy) known only from the type specimens collected by Huter, Porta and Rigo almost 150 years ago, is confirmed in the Italian flora. H. scorzonerifolium subsp. divaricatum was rediscovered in two locations both falling in the Lucanian side of the Pollino National Park. Notes on its taxonomy, nomenclature, distribution, ecology and conservation status are provided and a new detailed description of the taxon is given too.